(untitled) (Revista Internacional de Folkcomunicação, 2023)
This study reflects on the intertwined relationships between social movements, folk-communication language and the role of business in generating employment and income in the Entra Apulso Community in the Boa Viagem neighborhood, south of Recife-PE. The article is based on ethnographic research with the author’s observation while carrying out university extension projects in the location, and has a qualitative, as well as bibliographic, character. Folkcommunication is the methodological foundation from the title of the work, which presents the subaltern view regarding economic issues experienced by local residents and at the same time the sagacity of this social microcosm, an accurate portrait of a big house/slave Brazil, which passes to discover a new class format that is aware of its rights.